WAJAH TK BERBASIS ISLAM: KESIAPAN GURU DALAM MENERAPKAN PEMBELAJARAN STEM - Yubaedi Siron; Ayu Iis Nuryanah; Huri Huraerah; Nisa Fadhliyah Rahmani (Al Hikmah: Indonesian Journal of Early Childhood Islamic Education (IJECIE), 2020)
This research was conducted to describe the readiness of Islamic-based kindergarten teachers regarding STEM education. This research uses a qualitative approach. This research used a purposive sampling method to select the participants. The research participant consisted of 11 teachers who came from Islamic-based kindergartens. Participants were involved in semi-structured interviews. The qualitative data were analyzed by inductive content analysis. This case study results reveal knowledge, readiness, learning strategies, media, and challenges faced by teachers. There are differences in learning strategies, methods, and media used in implementing STEM in each Islamic school. The lack of knowledge and the low creativity of teachers is also an obstacle for schools in implementing STEM learning..